Characteristics of the Teren Bas Instrument of Orkes Kampoeng Wangak - Viktoria Friski Lestari; Ezra Deardo Purba; Rianti Mardalena Pasaribu (Gondang: Jurnal Seni dan Budaya, 2025)
Teren Bas is a distinctive musical instrument from Maumere that has developed from the village music traditions of East Flores. In the context of contemporary ethnic music, this instrument has undergone a transformation in both form and function through the musical practices of the group Orkes Kampoeng Wangak based in Yogyakarta. This study explores the characteristics of the Teren Bas instrument as performed by Orkes Kampoeng Wangak, particularly through the song "Gemu Fa Mi Re." Teren Bas is a unique Maumere instrument resembling a one-stringed contrabass, played using a stick in a percussive manner. The aim of this research is to identify the organological, acoustic, and musical characteristics of the Teren Bas from a musicological perspective. The method employed is qualitative-descriptive with a musicological approach. The findings indicate that Orkes Kampoeng Wangak is a contemporary ethnic music ensemble that blends Maumere traditions into a modern format. The Teren Bas is constructed from kemiri (candlenut) wood, producing a rounded and rhythmic bass sound. Its playing patterns include the styles of Kripso, Langgam, Mars, and Dolo-Dolo, which reflect the cultural roots of Maumere. In the arrangement of “Gemu Fa Mi Re,” the Teren Bas serves as the rhythmic core and a symbol of musical identity, creatively combined with other instruments such as the juk, benyol, violin, flute, and jimbe. The arrangement process integrates modern chord progressions, energetic musical structures, and local sound explorations typical of Maumere through both traditional and non-traditional instruments.